Tradition und Traditionsverhalten Literaturwissenschaftliche Zugänge und kulturhistorische Perspektiven - Toledo Flores, Karolin; Werle, Dirk; Reich, Philip (Kulturelles Erbe: Materialität - Text - Edition (KEMTE), 2021)
In Western cultural history, 'tradition' is one of the central concepts to describe processes of reception and their impact. Especially in literary studies, traditions are often claimed by stating, for example, that a particular text stands 'in the tradition' of another text. Nevertheless, coherent theoretical reflection is often lacking. This volume approaches the general question "What is tradition?" and the more specific question "How can one adequately speak about literary traditions?" by theorizing the premises of the concept and by discussing its theoretical capacity on the basis of case studies from various constellations throughout literary and cultural history.